Tanggung Jawab Notaris Dalam Pembuatan Minuta Yang Dibuat Berdasarkan Keterangan Palsu - Mas Maya Ramanti, Putu (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
In Article 1 paragraph (1) of laws No.2 of 2014 concerning the amendment to the Laws No. 30 of 2014 concerning the office of a notary states that a notary is a Public Official authorized to make an Aunthentic deed and has other authorities as set up in the legislation or under other laws. Deed made before a notary can be classified in two (2) kinds of certificates, namely partij deed/deed of the parties and the deed of relaas/officials. The problem discussed in this thesis is what is the legal regulation of the production of notarial deed in the legislation in Indonesia, what is the legal effect of a deed made based on false information by the parties involved. The type of research is the study of normative law because there is a conclict norm between the two regulation, the statute approach, the analytical and conceptual approach and the coparative approach. Sources of primary legal materials of legislation, secondary legal materials used in the studies may be in the form of books and articles in electronic format. The data collection was done through library research covering primary legal materials. Data processing and analysis of legal materials were done through descriptions of situationsor events. This technique did not search for or explain relations, did not test hypothesesor make predictions. The conclusion of the study demonstrates that notaries in running his or her office must pay attention to and must be subject to the Laws No. 30 of 2004 concerning the post of a notary which has been amended by the enactment of Laws No 2 of 2014 concerning the amendment to the Laws No 30 of 2004 concerning the office of a notary and ethical codes for a notary which constitutes applicable regulations for moral guidance for a notary profession. A deed that contains false information which is provided by the parties can be cancelled. Deed cancellation can be done by a notary if demanded by the parties who suffer losses.
Keywords: responsibility, notaries, deeds, false information